(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This research article examines the sources of Khorezm literature in European collections, including the works of Bobojon Sanoyi and Husayn Khorezmi. The article focuses on the literary heritage of Khorezm and its importance in Europe, and shows how important the preservation and research of such works is for past and present science, literature and culture. Bobojon Sanoyi (XII century) occupies an important place in Eastern literature with its "Hamsa". He is known for his love of industry, philosophy and thoughts on the spiritual path of man. This work is preserved in European archives and is of great importance in the study of Muslim literature and philosophy of the Middle Ages.